TEXTBOOKS ANALYSIS: ANALYZING ENGLISH AS A FOREIGN LANGUAGE (EFL) TEXTBOOKS FROM THE PERSPECTIVE OF INDONESIAN CULTURE - Gunantar, Devy Angga (Language Circle: Journal of Language and Literature, 2017)
Textbooks are very important parts in teaching and learning process. Both teachers and students, mostly, use them as the basic foundations of courses in the classrooms. Textbooks may not be able to fulfill all the needs of the teaching and learning process but their existence as teaching sources is still paramount. They become one of effective sources of learning used in teaching and learning process and as reflection of values and ideas of a person or nation. The aspect of culture can be supported by systematic and comprehensive textbooks. This research paper analyzes some textbooks used in one of Junior High Schools in Indonesia. The way the writer analyzed the textbooks was based on cultural perspective. This is mainly because, in learning English, Indonesian students should focus more on talking and discussing Indonesian culture in English rather than the English speaking countriesâ culture. To analyze and examine the cultural contents in the English textbooks, the writer followed the standards set by Bryam. Byramâs criterion is considered sufficient and comprehensive. This set of checklist is driven from the idea of cultural learning and teaching as an integral part of language education. The result shows that the textbooks being analyzed covered local or Indonesian culture. This findings accentuate the needs of revisiting English teaching materials to contribute to the improvement of English Textbooks in Indonesia.